2016
DOI: 10.1186/s13058-016-0672-x
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic silencing of CREB3L1 by DNA methylation is associated with high-grade metastatic breast cancers with poor prognosis and is prevalent in triple negative breast cancers

Abstract: BackgroundCREB3L1 (cAMP-responsive element-binding protein 3-like protein 1), a member of the unfolded protein response, has recently been identified as a metastasis suppressor in both breast and bladder cancer.MethodsQuantitative real time PCR (qPCR) and immunoblotting were used to determine the impact of histone deacetylation and DNA methylation inhibitors on CREB3L1 expression in breast cancer cell lines. Breast cancer cell lines and tumor samples were analyzed similarly, and CREB3L1 gene methylation was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
61
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 61 publications
6
61
0
Order By: Relevance
“…Genomic DNA was extracted from LC tissues and cell lines using a DNA extraction kit (Promega, USA). After quantification, 2 μg of DNA was treated with sodium bisulfate as previously reported [ 28 ], and used as the template DNA for PCR. The MSP primers were designed with the MethPrimer ( http://www.urogene.org/cgi-bin/methprimer/methprimer.cgi ) [ 29 ] and sequences were listed in Supplementary Table 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Genomic DNA was extracted from LC tissues and cell lines using a DNA extraction kit (Promega, USA). After quantification, 2 μg of DNA was treated with sodium bisulfate as previously reported [ 28 ], and used as the template DNA for PCR. The MSP primers were designed with the MethPrimer ( http://www.urogene.org/cgi-bin/methprimer/methprimer.cgi ) [ 29 ] and sequences were listed in Supplementary Table 2 .…”
Section: Methodsmentioning
confidence: 99%
“…For example, the number of genes has been reported to be methylated and consequently silenced, including tumor suppressor genes, such as secreted frizzled-related protein ( SFRP ), RASSF1A, WNT inhibitory factory factor 1 ( WIF1 ) inter-alpha-trypsin inhibitor heavy chain family member 5 (ITIH5), Dickkopf WNT signaling pathway inhibitor 3 ( DKK3 ), ATM serine/threonine kinase ( ATM ), long interspersed nuclear element 1 ( LINE1 ), cyclin-dependent kinase inhibitors ( CDKN2 and CDKN1B ), G1/S-specific cyclin-D2 ( CCND2 ), breast cancer 1 ( BRCA1 ), mutL homology 1 ( MLH1 ), glutathione S-transferase P ( GSTP1 ), homeobox protein ( HOXA5 ), cadherin-1 ( CDH1 ), metalloproteinase inhibitor 3 ( TIMP3 ), cAMP-responsive element-binding protein 3-like protein 1 ( CREB3L1 ) and hormone receptors ( ESR1 and PGR ). These genes have been shown to be involved in cell cycle regulation, DNA repair, cell detoxification, apoptosis and cell adhesion and invasion [ 38 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. The phospholipase A2 receptor (PLA2R1) is a transmembrane protein that plays a role in the clearance of phospholipase A2.…”
Section: Epigenetic Regulation Of Gene Signaling In Breast Cancersmentioning
confidence: 99%
“…CREB3L1 is frequently upregulated in luminal and HER2amplified breast cancer but not in TNBC [31]. However, recently, Bray Denard1 reported that TNBC tumours with high CREB3L1 expression have a high response rate to doxorubicin-based chemotherapy [32].…”
Section: Discussionmentioning
confidence: 99%